247 Single-Photon Emission Computed Tomography (SPECT) In Predicting Localisation of Parathyroid Adenomas: A Closed-Loop Prospective Study. (12th October 2021) - Ahmed, O; Gao, C; Buchanan, M; Pfleiderer, A; Al-lami, A
Abstract: Aim: to measure the sensitivity of SPECT in localising parathyroid adenomas particularly whilst attempting minimally invasive parathyroidectomy. Method: 2-cycles prospective study correlating SPECT and operative findings was conducted. All patients underwent ultrasound and SPECT, those with concordant findings on both modalities underwent minimally invasive parathyroidectomy, whilst patients with discordant findings on both modalities had central neck exploration. Following operative findings, recommendations of changing the SPECT reporting method such as surgically relevant structures adjacent to the lesion, such as the thyroid, were implemented. Following which, a second prospective study assessed the outcome of change. Results: In the first cycle, 20 patients underwent partial parathyroidectomy, either by open (n = 13), or minimally invasive (n = 7) approach. SPECT sensitivity was 85% (n = 17) in identifying the adenoma. Out of all histologically confirmed adenomas, SPECT identified all adenomas (n = 17) on the correct side and 41% (n = 7) on the correct level (superior vs. inferior parathyroid). In the second cycle following recommendation, 14 patients had surgery, 9 as minimally invasive and 5 as open approach. SPECT sensitivity was 79% (n = 11) for adenoma identification. Of all confirmed adenomas, SPECT identifying adenomas at the correct side increased to 91% (n = 10) and correct level to 91% (n = 10). Conclusions: SPECT alone is not yet regarded as gold standard in parathyroid adenoma localisation. The study has demonstrated that feedback to the radiologist of the operative findings may enhance its usefulness, particularly in attempting to proceed with a minimally invasive parathyroidectomy.